2021
DOI: 10.1016/j.ijscr.2021.106147
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive medulloblastoma initially mimicking idiopathic intracranial hypertension and Chiari I malformation: A case report

Abstract: Introduction Medulloblastoma (MDB) often causes signs and symptoms of elevated intracranial pressure (ICP) with imaging findings of mass lesion. Here, we report a case of MDB who initially presented with clinical features imitating idiopathic intracranial hypertension (IIH) and Chiari I malformation (CIM). Case presentation A 19-year-old man had clinical symptoms of elevated ICP without mass lesion on imaging. He was initially diagnosed with IIH and CIM, which underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 11 19 While some authors have demonstrated the presence of contrast-enhancing leptomeninges on CT 4 7 and MRI, 6 8 9 10 12 in our case, no variation was recognized after contrast administration both before and after the endoscopic procedure. Our neuroradiological investigations demonstrated only a Chiari-like malformation 11 16 with triventricular hydrocephalus 6 11 16 and nonspecific cerebellar swelling with some hyperintensities in FLAIR and T2-weighted sequences. 9 11 …”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“… 11 19 While some authors have demonstrated the presence of contrast-enhancing leptomeninges on CT 4 7 and MRI, 6 8 9 10 12 in our case, no variation was recognized after contrast administration both before and after the endoscopic procedure. Our neuroradiological investigations demonstrated only a Chiari-like malformation 11 16 with triventricular hydrocephalus 6 11 16 and nonspecific cerebellar swelling with some hyperintensities in FLAIR and T2-weighted sequences. 9 11 …”
Section: Discussionmentioning
confidence: 68%
“… 5 In most cases, it appears to be secondary to the primary mass. 7 16 Although subarachnoid seeding is common, occurring in approximately 33% of MB at the time of diagnosis, 5 purely diffuse leptomeningeal tumor spread without mass lesion in an adult patient is rare, 4 5 6 7 8 9 10 11 12 17 and has, to the best of our knowledge, been only reported few times in the literature, 4 5 6 7 8 9 10 11 12 and all the described patients had very unfavorable prognosis. 4 5 6 7 8 9 10 11 12 …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations